Transcendental Communication Strategies in Ruqyah Therapy: Unveiling the Power of Dialogue between Healers and Spiritual Entities - Homsatun, Atun (Al-MUNZIR, 2024)
Man can't get rid of his need to communicate in everyday life, whether it's interpersonal, interpersonal, group or mass communication and so is transcendental communication. This study aims to explain how the practitioner performs the rituals in order to be able to communicate with the jin during the ritualization process and describe how the impact occurs after the occurrence of tarnsendental communication between the jin and the jin. This research uses qualitative methods with a phenomenological approach. This study found that the strategy implemented by the practitioner in order to be able to communicate with the jin exists in three stages, namely, first, the formulation of the communication strategy. Second, the implementation relates to the outcome of the diagnosis. Third, the evaluation relating to the validity of the dialogue with the Jin. Further findings, the effect of transcendental communication covers three aspects that occur to the jin and the jin: the aspect of change of knowledge, the aspects of changes of attitude and the aspect of change in behavior. Keywords: Communication Strategy, Transcendental, Ruqyah.